Dispositional playfulness in young children: A cross‐sectional and longitudinal examination of the psychometric properties of a new child self‐reported playfulness scale and associations with social behaviour. Issue 4 (24th April 2020) - Fink, Elian; Mareva, Silvana; Gibson, Jenny L.
Abstract: Most research on children's play takes a context‐dependent, adult‐focused observational approach to the measurement of play. The current two studies present the development and psychometric properties of the Child Self‐Report Playfulness (CSRP) scale, which was presented via "puppet‐show" to two samples of children. Study 1, across 98 children between 5 and 7 years of age, showed that the items of the CSRP had good internal consistency, were stable across the 6‐week test–retest period and, for the most part, showed no differential item functioning across age, gender, and language ability. Study 2 involved a longitudinal sample of children followed from Reception (age 5, N = 244) to Year 1 (age 6). Findings revealed favourable psychometric properties using longitudinal confirmatory factor analysis and measurement invariance. Associations between child playfulness and teacher‐ and peer‐ratings of social behaviour were examined, and showed specific associations between playfulness and teacher‐rated play interaction, rather than social maturity, problem behaviour or social preference. Overall, the CSRP appears to be a promising approach to the measurement of dispositional playfulness in young children. Highlights: We developed a Child Self‐Reported Playfulness scale (CSRP) to assess children's perceptions of their own playfulness. Across two separate samples, the CSRP had favourable psychometric properties, was stable across the ages of 5 and 6 and showed specific associations with teacher‐rated play. The findings of the current studies have important implications for our understanding and measurement of children's play across development.